2011
DOI: 10.1002/iub.438
|View full text |Cite
|
Sign up to set email alerts
|

Ligand migration in the truncated hemoglobin of Mycobacterium tuberculosis

Abstract: SummaryThe truncated hemoglobin of Mycobacterium tuberculosis (Mt-trHbO) is a small heme protein belonging to the hemoglobin superfamily. Truncated hemoglobins (trHbs) are believed to have functional roles such as terminal oxidases and oxygen sensors involved in the response to oxidative and nitrosative stress, nitric oxide (NO) detoxification, O 2 /NO chemistry, O 2 delivery under hypoxic conditions, and long-term ligand storage. Based on sequence similarities, they are classified into three groups. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…Therefore, ligand migration from the outside towards the active site involves ligand diffusion, often occurring through a network of connected, internal sites. Extensive research has shown that such networks of internal cavities (pockets, packing defects) exist particularly in globular proteins, and has been confirmed for heme containing proteins including myoglobin (Mb) [1214], cytochrome b α 3 oxidase [15, 16], dimeric hemoglobin [8, 14], or truncated hemoglobins N and O [1719]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ligand migration from the outside towards the active site involves ligand diffusion, often occurring through a network of connected, internal sites. Extensive research has shown that such networks of internal cavities (pockets, packing defects) exist particularly in globular proteins, and has been confirmed for heme containing proteins including myoglobin (Mb) [1214], cytochrome b α 3 oxidase [15, 16], dimeric hemoglobin [8, 14], or truncated hemoglobins N and O [1719]. …”
Section: Introductionmentioning
confidence: 99%
“…Cohen and Schulten 15 used implicit ligand sampling to demonstrate different pathways in a variety of globins. Heroux, Mohan and Olsen 16 showed that a point mutation in a truncated hemoglobin could change the oxygen escape routes. In this study we apply locally enhanced sampling molecular dynamics 17 (LESMD) to visualize ligand binding in wildtype and six mutant structures of HbI.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine can mediate and defend against pathogenic microorganisms. This situation is possibly improved, because cytokine can effectively prevent microorganisms from absorbing iron (Heroux et al, 2011). Some experts believe that mycobacteria acquire iron from the iron-binding proteins of the host's own transferrin/ferritin.…”
Section: Discussionmentioning
confidence: 99%